Stereoselective synthesis of tetrahydroindolizines via catalytic formation of pyridinium ylides from diazo compounds - Day, Jonathan; McKeever-Abbas, Ben; Dowden, James (Wiley-VCH Verlag, 2016)
Commercially available iron (III) and copper (I) complexes catalyze new multicomponent cycloadditions between diazo compounds, pyridines and electrophilic alkenes to give alkaloid-inspired tetrahydroindolizidines in high yields and diastereoselectivities. Hitherto, catalytic formation of versatile pyridinium ylides from metal carbenes has been poorly developed; the broad utility demonstrated herein sets the stage for invention of further multicomponent reactions in future.